SEXUAL INTERCOURSE EUPHEMISMS IN THE GĨKŨYŨ LANGUAGE: A COGNITIVE LINGUISTICS APPROACH (The University of Nairobi Journal of Language and Linguistics, 2023)
The research on which this paper is based set out to identify the sexualintercourse euphemisms used in Gĩkũyũ, a Bantu language spoken in Kenya,then discuss the semantic and lexical processes used in those euphemisms,and, finally, point out the specific metaphors that underlie these latter. Toachieve these objectives, the research used data collected (using aninterview schedule) from 20 native Gĩkũyũ speakers. The euphemisms wereassigned to their corresponding semantic and lexical processes, and thendiscussed in terms of their correspondences between the source domain andtarget domain, two key concepts of the Conceptual Metaphor Theory. Thespecific metaphors behind those euphemisms were discussed. It transpiredfrom this discussion that men generally looked at sexual intercourse more asWORK, A GAME, WAR, FOOD and UTILITY, while women looked at it mainly asa form of COMPANIONSHIP.